Impact of a training intervention on use of antimicrobials in a teaching hospital - experiences from Malaysia - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Nordin, Mohamad Sahari; Satwi, Sapari; Rathor, Mohammad Yousuf; Md Aris, Mohd Aznan; Samsuddin, Niza (INSI Publications, 2012)
A quasi-intervention study was conducted to identify the patterns of antimicrobial use and to assess the effectiveness of an interactive training programme on antimicrobial prescribing for physicians in medical wards of a tertiary care hospital in Pahang, Malaysia. The period of data collection was four months in each of the pre-intervention and the post-intervention investigations from March through June in 2008 and in 2009 respectively. A total of 429 patients' treatment charts were reviewed: 209 in the first and 220 in the second investigations. Patients aged 13 years to 95 years. From March through June, 2008, (pre-intervention), an investigation of antimicrobial use was conducted at medical wards of the hhospital. A short, interactive training programme focussed on antimicrobial prescribing was then conducted for physicians in the studied hospital. The training materials, inter alia, Guide to Good Prescribing”, and How to Investigate Drug Use in Health Facilities, were utilized for the educational intervention. A second investigation was conducted later on in the same medical wards of the hospital. The core indicators of antimicrobial prescribing practices, some of the related clinical outcomes of antimicrobials utilization for the treatment of admitted patients in medical wards were specifically focused. Common antimicrobial practice patterns were evident in the medical wards of the hospital, with the most commonly used antimicrobials were the combination preparation of amoxicillin with clavulanate (augmentin). Generic prescribing was 54.3% and the intravenous route was the preferred r ute of administration (57.3%). The mean number antimicrobials received by the studied patients were 1.8 ( 0.9). The majority of them (53.6%) received two or more antimicrobials for their treatment. In post intervention phase, similar patterns of antimicrobial use were observed with a notable reduction in the mean number of antimicrobial agents used per patient (1.7  08).An interactive, focussed educational intervention programme, targeted at physicians, appears to have been effective in improving antimicrobial use in a medical wards of a tertiary care hospital in Malaysia.